Largazole inhibits ocular angiogenesis by modulating the expression of VEGFR2 and p21 - Qiu, Beiying (2022)
Ocular angiogenic diseases, characterized by abnormal blood vessel formation in the eye, are the leading cause of blindness. Although Anti-VEGF therapy is the first-line treatment in the market, a substantial number of patients are refractory to it or may develop resistance over time. As uncontrolled proliferation of vascular endothelial cells is one of the characteristic features of pathological neovascularization, we aimed to investigate the role of the class I histone deacetylase (HDAC) inhibitor Largazole, a cyclodepsipeptide from a marine cyanobacterium, in ocular angiogenesis. Our study showed that Largazole strongly inhibits retinal vascular endothelial cell viability, proliferation, and the ability to form tube-like structures. Largazole strongly inhibits the vessel outgrowth from choroidal explants in choroid sprouting assay while it does not affect the quiescent choroidal vasculature. Largazole also inhibits vessel outgrowth from metatarsal bones in metatarsal sprouting assay without affecting pericytes coverage. We further demonstrated a cooperative effect between Largazole and an approved anti-VEGF drug, Alflibercept. Mechanistically, Largazole strongly inhibits the expression of VEGFR2 and leads to an increased expression of cell cycle inhibitor, p21. Taken together, our study provides compelling evidence on the anti-angiogenic role of Largazole that exerts its function through mediating different signaling pathways.